Pedagoški pristop CLIL – izziv za profesionalni razvoj učiteljev tujega jezika na zgodnji stopnji šolanja - Pevec Semec, Katica (Revija za elementarno izobraževanje, 2015)
The CLIL Pedagogical Approach - Challenges for the Professional Development of Foreign Language Teachers of Young Learners. In this paper we are interested in knowing which options teachers attribute to CLIL providers, including modern didactic concepts of teaching and learning foreign languages, which are also based on the curriculum for foreign languages in the 2nd and 3rd grade of primary school. In doing so, we will rely on the key elements of the CLIL didactic concept by Coyle, which reflect multi-dimensionality. The multi-dimensional element of CLIL is a newly added value to teacher professional development in the project Drei Hände - Three hands - Tre mani. In this study, we found that among the 4 elements of CLIL represented, the strongest element was that of language (communication) and the least represented element was that of culture. Among the collective capabilities of teachers who implement CLIL, the ability to „learn to do” was represented most frequently.
Keywords: competences of teachers; CLIL; elementary school; multidimensionality